Geopolitik dalam membangun ketahanan nasional Indonesia - Fazri, Ray Muhammad (Maliki Interdisciplinary Journal, 2025)
National identity and geopolitics are two main pillars in the development and national resilience of a country, especially Indonesia. As a pluralistic archipelago. National identity reflects the identity of the nation, while geopolitics serves as a strategic guide in managing resources and geographical positions for national interests. This study aims to analyze the relationship between national identity and geopolitics and their contribution in maintaining the integrity and sovereignty of the Unitary State of the Republic of Indonesia (NKRI). The method used is a literature review with a descriptive-analytical approach. The results of the study show that strengthening national identity can be a foundation in facing global and regional geopolitical challenges, as well as being an important element in realizing the archipelago insight as a national perspective.